PENGARUH ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN SAHAM PERUSAHAAN OTOMOTIF DI INDONESIA TAHUN 2007–2010 - Widiati, Putri Kurnia (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
This study analyzed the effect of Economic Value Added (EVA), Market Value Added (MVA) of otomotif companies Stock return listed on stock exchanges Indonesia, because otomotif companies have an important position on Indonesian Economics.Population of this research are otomotif company that listed on the Stock Exchange of Indonesia from 2007â€“2010 with sensus sampling method and multiple regresion analysis to analyzed. For the parsial side Market Value Added (MVA) has an influence to stock return of Otomotif Company that listed on the Stock Exchange. To get the trust from investor, otomotif company should have good performance with a good value of Market Value Added, because Market Value Added has significant effect to stock return; and have a good prediction about another factor that influence the stock return wich used histories data for the indicator.Â